Women's participation in community development in rural Ghana: The effects of colonialism, neoliberalism, and patriarchy. Issue 3 (27th May 2022) - Gyan, Charles; Mfoafo-M'Carthy, Magnus
ABSTRACT: Women's empowerment and gender equality have been given attention by development practitioners and communities over the last two decades. Studies show, however, that in the face of the increase attention to gender equality in community development, women's advancement, and participation in both developed and developing countries are restricted. The situation of women involvement in the community development process in Ghana is abysmal. The purpose of this study was to ascertain how colonialism, patriarchy and neoliberalism serve as barriers to women within community development processes in rural Ghana. This paper is approached from transnational feminist perspective. A total of twelve (12) women from three randomly selected rural communities in Ghana were interviewed about their community development experiences. The findings implicate Western influence and structural factors in the low participation of women in community development processes in rural Ghana. This study found that Western interference in the form of the superimposition of a neoliberal capitalist agenda has had a negative consequence on the level of participation of women in their communities. This ideology has imbued in women individualistic ideals to the detriment of traditional communal life. The women were particularly disadvantaged by the reliance on level of education and fluency in English, as requirements for local government positions since English is the national business language. The existing patriarchal norms and values in rural communities such as traditional gender roles and "name calling" militate against women within the context of community development. Western interference, colonialism, patriarchy, and capitalist ideologies continue to hinder the involvement of women in the development of their communities. It is therefore important to address these issues to help better the lives of women in rural Ghana.